Emerging gender issues in Vietnam pig value chain - Nguyen Thi Thinh; Lapar, Ma. Lucila; Galiè, Alessandra (Kasetsart University, 2017)
Using a broad systematic literature review of peer reviewed publications and grey literature, the paper summarizes the most relevant gender issues in the pig value chain of Vietnam, and the ways in which these could be addressed. Specifically, women were found to face more severe constraints than men in accessing productive resources, markets and services. They have limited access to land use rights and therefore have limited access to resources for pig production. Besides, time constraints and cultural norms hinder women from actively participating in trainings and extension activities. Several projects/programs have been undertaken to help reduce the gender gaps. Lessons learnt from successful projects indicate that approaching women farmers via the Women’s Union is an effective way to increase the active participation of women in trainings. Identifying and providing technical trainings that meet specific needs of women farmers could lead to productivity increase. Besides, it is important to facilitate collaboration and dialogue between men and women to encourage men’s support of women’s empowerment and to improve the positive impacts of project interventions.